Limb Preservation Surgery in Musculoskeletal Tumors. Use of Liquid Nitrogen. "A novel and inexpensive reconstruction technique" First cohort of patients in Uruguay. - Bianchi, Gottardo; Casales, Nicolás; Silveri, Claudio; Gaiero, Leticia; Stoppiello, Pablo; Pérez, María Elena; Rey, Rogelio; Francescoli, Luis (Cirugía del Uruguay, 2020)
Introduction: Limb-sparing surgery is the standard treatment in the management of musculoskeletal tumors. The problem that the surgeon faces is reconstruction after a wide resection. There are various techniques such as endoprostheses, allografts and autografts, among others. In 1999 in Japan, Tsuchiya, et al developed the biological reconstruction technique using liquid nitrogen (LN). The objective of the following work is to present the first cohort of patients treated with this technique in our country. Also, analyze the following parameters: local recurrence, consolidation times, autograft survival, and functional evaluation at the end of follow-up. Methodology: A retrospective study was conducted from August 2015 to June 2019 of patients treated with frozen autograft in LN. All were evaluated in a multidisciplinary team and treated by the same surgical team. A total of 19 cases were registered, 13 were included for evaluation, the rest being excluded because they had less than 6 months of follow-up. The technique consists of tumor resection with wide margins, exposing the tumor to an immersion cycle in NL at -196 degrees Celcius for 20 minutes, then progressive heating for 15 minutes at room temperature and 10 minutes in distilled water. Achieving eradication of tumor cells by cryotherapy. Followed by reimplantation of the frozen bone and fixation with osteosynthesis material. In the evaluation, the local recurrence was evaluated clinically and imaging. Consolidation was assessed as defined by Zekry et al: patient without pain when ambulating and osteotomy lines are not visible or there is an obvious callus in 3 of the cortices in the anteroposterior and lateral approaches. The survival of the autograft was evaluated according to whether or not it was necessary to remove it. Results: At the end of the follow-up, all the patients were alive, none of the patients with localized disease had developed distant metastases. A patient with local recurrence in soft tissues was registered. Consolidation was achieved in 83% of the patients, with a mean of 6.7 months. It was necessary to remove the graft in 3 cases, two due to deep infection and the other due to joint collapse. The functional evaluation according to the average MSTS-ISOLS score was 73.8% (range 13-100%). This average was 89.9% (63-100%) in the 10 patients who kept the autograft. Conclusions: The frozen autograft technique in LN is a very good reconstruction option in musculoskeletal tumors. It is a technique that is easy to access, low in cost and maintains the properties of osteoconduction and osteoinduction. Our series presents similar results to published studies in terms of local recurrence, consolidation and functional score.